Detection of sodium deficiency in crossbred Friesian X Zebu (Boran) calves fed roughage - based diets using faecal Na contents as an indicator - Khalili, M.; Capper, B.; Lindgren, E. (Swedish University of Agricultural Sciences, 1991)
Two roughage-based diets composed of equal parts of roughage and concentrate were fed to 45 crossbred Friesian X Zebu (Boran) calves. The roughages were either oat-vetch hay or barley straw. 25 animals were fed the diet based on oat-vetch hay and 20 the barley straw-based diet. Within these groups animals were grouped according to liveweight and then randomly allocated to 5 treatments of Na Kg DM as Na Cl. The feed of all calves was restricted to 2.7 percent of liveweight per day. Diets were fed individually for 98 days following a 14 day adaptation period when no Na Cl was provided. the investigations were designed to study the possibility of using faecal Na concentrations as an indicator of Na deficiency in cattle. The calves fed the oat-vetch hay based diets given the highest level of Na showed a significantly higher LW gain than the control group. Variation in the salivary Na within each treatment was high and the effect of Na Cl on the concentrations of Na in plasma in the calves fed either oat-vetch hay or barley straw based diets did not change. The effect of Na supplementation on faecal Na was significant for both diets. Concentration of Na in the faeces was below 1g kg DM only in the unsupplemented diets.